2004
DOI: 10.4038/jnsfsr.v32i3-4.2431
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Method for the Determination of Propanil in a Simulated Rice Field Environment

Abstract: Amperometric experiments conducted with commercial samples of Propanil a t Fe(II1)TPPCl-modified glassy carbon electrodes in 1:3 CH,CN/H,O result in smooth ampemgrams producing linear calibration curves. The amount of Propanil present in effluent water leached through soil of a model rice cultivation in a polytunnel can be accurately determined using this method. The concentration of Propanil in water samples collected within a period of 8 h decreased from (6.70 + 0 . 0 6 )~1 0 -~ mol dm-$ to (8.10 + 0.08)x1O4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…They obtained a detection limit of 0.97 mM, very close to the 0.99 mM found here at the PANI-b-CD/fMWCNT film electrode; the analytical sensitivity of 0.0327 A M À 1 cannot be directly compared since the electrode area is not specified in [27], but is lower by a factor of around 4 than that here, if electrode areas are the same or similar.…”
Section: Analytical Applicationsupporting
confidence: 78%
See 1 more Smart Citation
“…They obtained a detection limit of 0.97 mM, very close to the 0.99 mM found here at the PANI-b-CD/fMWCNT film electrode; the analytical sensitivity of 0.0327 A M À 1 cannot be directly compared since the electrode area is not specified in [27], but is lower by a factor of around 4 than that here, if electrode areas are the same or similar.…”
Section: Analytical Applicationsupporting
confidence: 78%
“…The only electroanalytical determination of MCPA found in the literature tests MnO 2 -modified carbon paste electrodes and Mnmodified glassy carbon electrodes, of which the former are better [27]. They obtained a detection limit of 0.97 mM, very close to the 0.99 mM found here at the PANI-b-CD/fMWCNT film electrode; the analytical sensitivity of 0.0327 A M À 1 cannot be directly compared since the electrode area is not specified in [27], but is lower by a factor of around 4 than that here, if electrode areas are the same or similar.…”
Section: Analytical Applicationmentioning
confidence: 99%
“…Additionally, it has been shown that MPEs have the ability for selective electrocatalysis of bromo-substituted aromatic substances depending on the position of substitution (50). Another step that has been taken further towards real application in the field of pesticide detection is the use of MPEs to determine the levels of propanil in simulated rice field environment by amperometry (51) and to monitor the activity of propanil by cyclic voltammetry (52). Electrodes modified with free base porphyrins do not produce significant current response in these detections proving the necessity of a metal ion at the center of the porphyrin molecule for electrocatalysis of halogenated aromatic hydrocarbons.…”
Section: Electrochemical Detection Of Halogenated Aromatic Substancesmentioning
confidence: 99%
“…The goal of this research is to study the fate of propanil in a simulated rice field by means of a kinetic model for the determination and quantification of its primary degraded product, 3,4-DCA. As propanil is not electroactive at bare electrode surfaces, its direct electrochemical determination is not possible and consequently, electrodes modified with metalloporphyrin catalysts have been reported as a reliable means for its detection (Priyantha & Weerabahu, 1996;Priyantha et al, 2004). On the other hand, electroactivity of 3,4-DCA makes it possible to investigate the fate of propanil through the detection of 3,4-DCA.…”
Section: Introductionmentioning
confidence: 99%